Arginine deiminase pathway enzymes: evolutionary history in metamonads and other eukaryotes - Novák, Lukáš; Zubáčová, Zuzana; Karnkowska, Anna; Kolisko, Martin; Hroudová, Miluše; Stairs, Courtney W; Simpson, Alastair G B; Keeling, Patrick J; Roger, Andrew J; Čepička, Ivan; Hampl, Vladimír (BMC evolutionary biology, 2016)
BACKGROUND: Multiple prokaryotic lineages use the arginine deiminase (ADI) pathway for anaerobic energy production by arginine degradation. The distribution of this pathway among eukaryotes has been thought to be very limited, with only two specialized groups living in low oxygen environments (Parabasalia and Diplomonadida) known to possess the complete set of all three enzymes. We have performed an extensive survey of available sequence data in order to map the distribution of these enzymes among eukaryotes and to reconstruct their phylogenies. RESULTS: We have found genes for the complete pathway in almost all examined representatives of Metamonada, the anaerobic protist group that includes parabasalids and diplomonads. Phylogenetic analyses indicate the presence of the complete pathway in the last common ancestor of metamonads and heterologous transformation experiments suggest its cytosolic localization in the metamonad ancestor. Outside Metamonada, the complete pathway occurs rarely, nevertheless, it was found in representatives of most major eukaryotic clades. CONCLUSIONS: Phylogenetic relationships of complete pathways are consistent with the presence of the Archaea-derived ADI pathway in the last common ancestor of all eukaryotes, although other evolutionary scenarios remain possible. The presence of the incomplete set of enzymes is relatively common among eukaryotes and it may be related to the fact that these enzymes are involved in other cellular processes, such as the ornithine-urea cycle. Single protein phylogenies suggest that the evolutionary history of all three enzymes has been shaped by frequent gene losses and horizontal transfers, which may sometimes be connected with their diverse roles in cellular metabolism.
Keywords: Carbamate kinase; Metabolic Networks and Pathways; Arginine; Arginine deiminase; metabolické sítě a dráhy; Preaxostyla; Metamonada; Evolution, Molecular; molekulární evoluce; Archaea; Phylogeny; Hydrolases; arginin; hydrolasy; fylogeneze; Ornithine transcarbamylase; Protists; Diplomonadida; Eukaryota